Inflammation mechanism and research progress of COPD - Xu, Jiao; Zeng, Qingyue; Li, Shuangqing; Su, Qiaoli; Fan, Hong (Frontiers in Immunology, 2024)
Chronic obstructive pulmonary disease (COPD) is a common respiratory disease characterized by irreversible progressive airflow limitation, often manifested by persistent cough, sputum production and other respiratory symptoms that pose a serious threat to human health and affect the quality of life of patients. The disease is associated with chronic inflammation, which is associated with the onset and progression of COPD, but anti-inflammatory therapy is not first-line treatment. Inflammation has multiple manifestations and phenotypes, and this heterogeneity reveals different patterns of inflammation, making treatment difficult. This paper aims to explore the direction of more effective anti-inflammatory treatment by analyzing the nature of inflammation and the molecular mechanism of disease occurrence and development in COPD patients, and to provide new ideas for the treatment of COPD patients.